2006
DOI: 10.1007/s00586-005-0022-7
|View full text |Cite
|
Sign up to set email alerts
|

Discriminative validity and responsiveness of the Oswestry Disability Index among Japanese outpatients with lumbar conditions

Abstract: The Oswestry Disability Index (ODI) is one of the most used assessment scales for patients with spine conditions, and translations into several languages have already been available. However, the scale's discriminative validity and responsiveness to the clinical change was somewhat understudied in these translated versions of the ODI. In this study, we independently developed a Japanese version of the ODI, and tested its discriminative and responsive performances among outpatients with various spinal condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 29 publications
2
14
0
1
Order By: Relevance
“…If so, then a relationship with the baseline findings is necessary for further extrapolation to a long-term outcome. 39 There is some association between the elements of the PBSI and the outcome measures ODI/NDI and SF-36 PCS, an association that, although statistically significant, was only fair to moderate, 40 a finding that is consistent with previous studies that found that the strongest correlation between instruments is in the SF-36 physical function subscale in English, 41 Japanese, 42 and Turkish. 43 The weakest association in our study was between the ODI and the mental health component of the SF-36.…”
Section: Discussionsupporting
confidence: 90%
“…If so, then a relationship with the baseline findings is necessary for further extrapolation to a long-term outcome. 39 There is some association between the elements of the PBSI and the outcome measures ODI/NDI and SF-36 PCS, an association that, although statistically significant, was only fair to moderate, 40 a finding that is consistent with previous studies that found that the strongest correlation between instruments is in the SF-36 physical function subscale in English, 41 Japanese, 42 and Turkish. 43 The weakest association in our study was between the ODI and the mental health component of the SF-36.…”
Section: Discussionsupporting
confidence: 90%
“…The accuracy (or discriminatory ability) of tests with AUCs 0.50-0.70 is generally considered low, between 0.70 and 0.90, moderate, and over 0.90, high [23]. The AUCs for the COMI were comparable to or even higher than those previously reported in the literature for back-specific instruments such as the Oswestry Disability Index (AUC 0.82-0.85) [6,13,16], the RolandMorris Disability Questionnaire (AUC 0.84) [16], or the pain intensity visual analog scale (AUC 0.88) [16] in patients undergoing spine surgery; they were also slightly higher than the AUC reported for the COMI during its initial validation studies in surgical patients (AUC 0.82) [15]. In the present study, individual ''improvement'' was predicted (with 81% sensitivity and 83% specificity) by a reduction in COMI score of 2.2 points or more.…”
Section: Discussionmentioning
confidence: 64%
“…The responsiveness of the ODI has been compared between a number of different populations and context [3,5,10,12,15,24]. These studies have estimated an SRM between 0.3 and 1.2 for the ODI [5,9,10,15,24].…”
Section: The Srm Of the Odi-chinesementioning
confidence: 99%